2009
DOI: 10.1038/aps.2009.76
|View full text |Cite
|
Sign up to set email alerts
|

Cellular trafficking of nicotinic acetylcholine receptors

Abstract: Nicotinic acetylcholine receptors (nAChRs) play critical roles throughout the body. Precise regulation of the cellular location and availability of nAChRs on neurons and target cells is critical to their proper function. Dynamic, post-translational regulation of nAChRs, particularly control of their movements among the different compartments of cells, is an important aspect of that regulation. A combination of new information and new techniques has the study of nAChR trafficking poised for new breakthroughs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…Studies have shown that nAChRs change their cellular expression in response to chronic nicotine exposure in culture and in vivo 2830 . In order to test the functionality of the epitope-tagged receptor clones and to measure nAChR plasma membrane expression we performed on-cell ELISA with non-permeabilized cells after overnight exposure of the cells to vehicle or 1 mM nicotine (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that nAChRs change their cellular expression in response to chronic nicotine exposure in culture and in vivo 2830 . In order to test the functionality of the epitope-tagged receptor clones and to measure nAChR plasma membrane expression we performed on-cell ELISA with non-permeabilized cells after overnight exposure of the cells to vehicle or 1 mM nicotine (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed measures of smoking status such as carbon monoxide, nicotine, or cotinine are needed to assess their effects on [ 18 F]nifene binding. Lastly, recent studies have reported on cellular trafficking of nAChR (reviewed in St John, ). Since [ 18 F]nifene exhibited relatively fast kinetics which is partially attributed to the lower basicity of the 3‐pyrrolinyl ring, our expectation is that it may not be sequestered in intracellular vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, RIC-3 has an additional role of transporting the receptor to the surface. In fact, since proper assembly is a pre-requisite for exit of the receptor from the ER [42] the sole ability of RIC-3 to enhance receptor assembly could promote its release from the ER and procession along the secretory pathway.…”
Section: Discussionmentioning
confidence: 99%